Efek Pendidikan Anak Usia Dini (PAUD) Bagi Kemampuan Interaksi Sosial Anak - Tri Sakti Widyaningsih; Tamrin Tamrin (FORIKES, 2020)
Background: Given the importance of early childhood education in child growth and development, the role of child caregivers in the school area community needs to conduct research on how management provides good stimulation when children enter pre-school age by providing an overview of the effectiveness of early childhood education (PAUD) on interaction ability Children Social at RA Islamic Tunas Bangsa 4 Semarang City. Methods: This study aims to determine the effectiveness of Early Childhood Education (PAUD) on the Social Interaction Ability of Children in RA Islamic Tunas Bangsa 4 Semarang City. The type of research used was quantitative with non-experimental used a cross-sectional design where the researcher seeks to analyze the effectiveness of children's social interaction skills assessed through the snake and ladder game intervention between groups of children who have attended PAUD and children who do not participate in PAUD in RA Islamic Tunas Bangsa 4 Semarang City by involving all children who fall into the criteria, according to the needs of the researcher. The population in this study were 57 children at kindergarten (TK A) in RA Islamic Tunas Bangsa 4 Semarang City. The sample in this study were members of the population who met the inclusion and exclusion criteria of the study sample, as many as 36 children. Results: The study used the Chi Square analysis test and statistically the p value was 0.001 (